2015
DOI: 10.1259/bjr.20140596
|View full text |Cite
|
Sign up to set email alerts
|

Patients with severe emphysema have a low risk of radiation pneumonitis following stereotactic body radiotherapy

Abstract: Little is known about the association between RP and pulmonary emphysema. Patients with severe emphysema had lower risk of RP than those with no underlying lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
(19 reference statements)
2
17
1
Order By: Relevance
“…14,15,22,23 Recently, the risk factors of RP after SBRT in patients with lung tumours have been investigated, 19,[22][23][24][25][26][27][28][29] and some studies reported about the clinical and dosimetric risk factors of RP. 21,[29][30][31][32][33][34][35][36][37][38][39][40][41][42] Table 7 summarizes published reports of the clinical and dosimetric risk factors associated with Grade 2 or worse RP after SBRT.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,22,23 Recently, the risk factors of RP after SBRT in patients with lung tumours have been investigated, 19,[22][23][24][25][26][27][28][29] and some studies reported about the clinical and dosimetric risk factors of RP. 21,[29][30][31][32][33][34][35][36][37][38][39][40][41][42] Table 7 summarizes published reports of the clinical and dosimetric risk factors associated with Grade 2 or worse RP after SBRT.…”
Section: Discussionmentioning
confidence: 99%
“…This transgenic mouse line was protected from fibrosis and mortality associated with bleomycin-induced lung injury. Furthermore, the risk of radiation pneumonitis was lower in patients with severe emphysema, such as the patients in our study, than that in patients with no underlying lung disease [18]. However, this is a hypothesis, and we intend to test this hypothesis in future studies.…”
Section: Discussionmentioning
confidence: 70%
“…Primary radiation therapy might be proposed for patients with emphysema, impaired lung function and NSCLC but this strategy lacks the beneficial effect of lung volume reduction. Radiation therapy shows only few complications [i.e., pneumonitis (35)] but our patients after concomitant cancer resection and LVRS profit from low morbidity as well. LVRS is safe and effective in all types of emphysema morphology and therefore cancer resection heterogeneous and even in intermediately heterogeneous emphysema should be taken into account (18,20,36).…”
Section: Discussionmentioning
confidence: 94%